Arithmetic-Like Reasoning in Wild Vervet Monkeys: A Demonstration of Cost-Benefit Calculation in Foraging - Tsutsumi, Sayaka; Ushitani, Tomokazu; Fujita, Kazuo (International Journal of Zoology, 2011)
Arithmetic-like reasoning has been demonstrated in various animals in captive and seminatural environments, but it is unclear whether such competence is practiced in the wild. Using a hypothetical foraging paradigm, we demonstrate that wild vervet monkeys spontaneously adjust their “foraging behavior” deploying arithmetic-like reasoning. Presented with arithmetic-like problems in artificially controlled feeding conditions, all the monkeys tested attempted to retrieve “artificial prey” according to the quantity of the remainder when the task involved one subtraction only (i.e., “2−1”), while one monkey out of four did so when it was sequentially subtracted twice (i.e., “2−1−1”). This monkey also adjusted his “foraging behavior” according to the quantity of the reminder for a task requiring stepwise mental manipulation (i.e., “(2−1)−1”), though the results became less evident. This suggests that vervet monkeys are capable of spontaneously deploying mental manipulations of numerosity for cost-benefit calculation of foraging but that the extent of such capacity varies among individuals. Different foraging strategies might be deployed according to different levels of mental manipulation capacity in each individual in a given population. In addition to providing empirical data, the current study provides an easily adaptable field technique that would allow comparison across taxa and habitat using a uniform method.